Oil Extraction from “Morelos Rice” Bran: Kinetics and Raw Oil Stability - J. Zúñiga-Diaz; E. Reyes-Dorantes; A. Quinto-Hernandez; J. Porcayo-Calderon; J. G. Gonzalez-Rodriguez; L. Martinez-Gomez (Journal of Chemistry)
“Morelos rice” is a variety of rice with certificate of denomination of origin. It is a large grain of opaque appearance and extra large size that is grown exclusively in Morelos state (Mexico). Thus, the quality and characteristics of its rice bran may affect the kinetic of the extraction process of its oil as well as its stability. Therefore, this work is oriented to determine the extraction kinetics of its oil and its oxidative stability. The latter one is obtained through the proposal of a method based on open-circuit potential measurements. The results showed that the rice bran has 21.44% of raw oil, with a chemical composition (based on fatty acids) of 48.48% oleic acid, 35.26% linoleic acid, and 14.54% palmitic acid, as well as a free fatty acid content of 8.15%. A high percentage of its oil content can be recovered in a short time at room temperature, and its extraction kinetics is a function of both the washing and the diffusion of its oil. Under storage conditions the raw oil has a high stability, at least 8 months, and its oxidative stability was of 24, 9, and 7 hours at 50°C, 80°C, and 110°C, respectively.